A Pilot Study on Serial Nerve Ultrasound in Miller Fisher Syndrome - Hsueh, Hsueh-Wen; Chang, Kai-Chieh; Chao, Chi-Chao; Hsieh, Sung-Tsang (Frontiers in Neurology, 2020)
Objective: Miller Fisher syndrome (MFS) is predominantly a clinical diagnosis, with classic triad of ophthalmoplegia, ataxia and generalized reduced reflexes. Previous studies in chronic and acute immune-mediated neuropathies indicated that ultrasound, may help to detect changes that could correspond with disease activity. We studied the feasibility of serial nerve ultrasound in MFS, using a and healthy controls. Methods: All MFS patients (n=5) and healthy controls (n=18), underwent a standardized sonographic protocol that evaluated nerve sizes of facial, large arm and leg nerves, and spinal nerve roots. All MFS patients underwent routine ancillary investigations, including electrodiagnostic testing and for presence of anti-GQ1b antibodies. In addition, all MFS patients had 2nd, and 3rd clinical and sonographic evaluation at 14 and 90 days from onset. Results: The width of the facial nerve was significantly larger in the MFS group than in the control group (MFS: 1.19 ± 0.31 mm vs. normal: 0.67 ± 0.13 mm, P = 0.01). The size of the cervical roots and the nerves in the limbs were similar between the two groups. Two patients’ facial nerve size subsided with time, but the decrease in other nerves’ sizes were not obvious. Conclusion: Our study showed that serial nerve ultrasound studies are feasible in MFS, and can capture changes in facial nerve size that could complement routine diagnostic tests. Further studies are warranted to determine and compare its test characteristics in MFS.